2005
DOI: 10.1016/j.jacc.2005.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Muscle Dysfunction Attenuates Ischemic Mitral Regurgitation in Patients With Localized Basal Inferior Left Ventricular Remodeling

Abstract: Papillary muscle dysfunction, reducing its longitudinal contraction to induce leaflet tethering, attenuates ischemic MR in patients with basal inferior LV remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
36
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 37 publications
(30 reference statements)
4
36
0
1
Order By: Relevance
“…Though IMR is a complex entity and a role for restricted leaflet motion, [22][23][24] annular dilatation, 25 papillary muscle (PM) dysfunction, 26 and many other alterations [27][28][29][30][31] have been postulated by different authors, we do agree with Levine and Schwammenthal. 27 that level of leaflet coaptation, then the possibility of MR, is finally determined by "tethering distance," which is defined as the distance between the PM and the mitral annulus; and its value here is the resultant of two ischemic changes: the altered bearing point of the PM base, and the altered length of the PM.…”
Section: Discussionsupporting
confidence: 81%
“…Though IMR is a complex entity and a role for restricted leaflet motion, [22][23][24] annular dilatation, 25 papillary muscle (PM) dysfunction, 26 and many other alterations [27][28][29][30][31] have been postulated by different authors, we do agree with Levine and Schwammenthal. 27 that level of leaflet coaptation, then the possibility of MR, is finally determined by "tethering distance," which is defined as the distance between the PM and the mitral annulus; and its value here is the resultant of two ischemic changes: the altered bearing point of the PM base, and the altered length of the PM.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, it is assumed that the impact of the systolic dimension is not as great when the diastolic dimension fails to affect the increasing MR. At an intensity of 150% AT, the LV dimension increased to a greater extent. Some studies suggest that in heart disease papillary muscle dysfunction causes tethering of the mitral valve as a result of remodeling of LV, and that this is the main mechanism of functional MR. [23][24] In our study, we used LV dilatation as a measure of the degree of LV remodeling, which means that, at an exercise level of 150% AT, an increase in the LV dimension seems to be one of the mechanisms responsible for worsening of tethering and thus worsening functional MR.…”
Section: Mechanisms Of Exercise-induced Mrmentioning
confidence: 99%
“…13 Other studies have suggested that papillary muscle dysfunction worsens tethering of the mitral valve, 15,16 even though recent studies suggest that papillary muscle dysfunction because of ischemic heart disease decreases tethering of the mitral valve. 17,18 The present study suggests that worsening of functional MR correlated only with the shape of the LV; that is, remodeling of the LV seemed to be the main mechanism of functional MR.…”
Section: Mechanisms Of Worsening Functional Mr During Exercisementioning
confidence: 55%
“…[13][14][15][16] Also, recent studies have suggested that remodeling of the LV is one of the main mechanisms of functional MR. 17,18 Here, we investigated LV deformation and studied how it relates to functional MR during exercise in patients with chronic heart failure (CHF).…”
mentioning
confidence: 99%